Apoplastic immunity in plants: A powerful weapon against plant pathogens - Sujhee, P; Raji, P (Plant Science Today, 2026)
Apoplastic immunity is a formidable first line of defence that plants use against invading pathogens at the extracellular interface. The apoplast, which includes the cell wall matrix, intercellular gaps and xylem vessels, serves as a dynamic battlefield for both host monitoring and pathogen attack. This compartment not only facilitates vital physiological activities like water, mineral and nutrient movement, but it also houses a wide range of defence molecules such as antimicrobial proteins, hydrolytic enzymes, secondary metabolites and reactive oxygen species (ROS). Upon pathogen entrance, cell surface-localised pattern recognition receptors (PRRs) identify conserved pathogen-associated molecular patterns (PAMPs), triggering PAMP-triggered immunity (PTI). This identification swiftly triggers signalling cascades involving calcium influx, mitogen-activated protein kinase (MAPK) pathways, apoplastic oxidative burst and ion fluxes, all of which work together to build cell wall barriers and limit pathogen proliferation. Furthermore, defence-related phytohormones, most notably salicylic acid (SA), jasmonic acid (JA) and ethylene (ET) coordinate local and systemic responses, boosting antimicrobial compound accumulation and defence gene activation.